An explanation of or-deletions and other paradoxical disjunctive inferences - Rasga, Célia (2022)
Some inferences of the sort: A or B; therefore A, which are invalid in standard logics, are sensible in life: You can enter now or later; therefore, you can enter now. That these "or-deletions" follow necessarily or only possibly is a by-product of a theory of mental models. Its semantics for "or" refers to conjunctions of possibilities holding in default of knowledge to the contrary. It predicts new sorts of or-deletion, such as: He likes to drink red wine or white wine. So, he likes to drink red wine. and: You are permitted to do only one of the following: You can enter now. You can enter later. Therefore, you are permitted to enter now. They are invalid in standard logics, and neither previous pragmatic nor semantic theories predicted them. Four experiments corroborated their occurrence.